Discrepancies in assessing undergraduates’ pragmatics learning - Oscar Ndayizeye (REID (Research and Evaluation in Education), 2017)
The purpose of this research was to reveal the level of implementation of authentic assessment in the pragmatics course at the English Education Department of a university. Discrepancy Evaluation Model (DEM) was used. The instruments were questionnaire, documentation, and observation. The result of the research shows that respectively, the effectiveness of definition, installation, process, and production stages in logits are -0.06, -0.14, 0.45, and 0.02 on its aspect of the assessment methods’ effectiveness in uncovering students’ ability. Such values indicate that the level of implementation fell respectively into ‘very high’,’high’, ‘low’, and ‘very low’ categories.  The students’ success rate is in ‘very high’ category with the average score of 3.22. However, the overall implementation of the authentic assessment fell into a ‘low’ category with the average score of 0.06. Discrepancies leading to such a low implementation are the unavailability of the assessment scheme, that of scoring rubric, minimal (only 54.54%) diversification of assessment methods, infrequency of the lecturer’s feedback on the students’ academic achievement, and the non-use of portfolio assessment.